STRATEGI PETANI HUTAN RAKYAT DAN KONTRIBUSINYA TERHADAP PENGHIDUPAN DI KABUPATEN GUNUNGKIDUL - Silvi Nur Oktalina; San Afri Awang; Priyono Suryanto; Slamet Hartono (Universitas Gadjah Mada, 2015)
The land ownership of smallholder private forest farmers is relatively narrows, so some reseachersargue that the forest product is not appropriate to fulfill daily needs. To increase and spread the privateforest management risk, farmers diversify crops into several species. In order to identify the farmerstrategy through optimizing the land, we developed household survey for 90 respondents from 3villages in Batur Agung zone, Ledok Wonosari zone and Pegunungan Seribu zone. The survey resultsshowed that private forest utilization by agroforestry is a type of local wisdom, as farmers ‘strategy tofulfill the farmers’ need. Private forest contribution toward total income in Gunungkidul is 13-40%. Thebiggest contribution for farmer in Batur Agung zone and Ledok Wonosari is from trees (59-61%), whilefor farmer in Pegunungan Seribu is from crops (59%).